2000
DOI: 10.1038/sj.jhh.1000983
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and hypertension physiopathology and therapeutics

Abstract: Diabetes mellitus by itself, is a frequent and increasing public health problem. The prevalence in most Western countries varies between 2 to 5% and it is rapidly increasing in Asiatic countries due to changes in dietary habits during the last years. The association between diabetes mellitus and hypertension has been described in 60 to 65% of diabetics. In hypertension we find insulin resistance mainly in skeletal muscle involving the conversion of glucose to glycogen independently of blood flow. The degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 14 publications
(16 reference statements)
3
39
0
1
Order By: Relevance
“…6,7 Interestingly, recent studies have shown that elevated systolic BP is present in almost all individuals with newly diagnosed DM. 8 One can only guess the future perspectives and magnitude of the situation given the global prevalence of DM and projections for 2030, 9 as well as the global challenge of hypertension over the next couple of decades.…”
mentioning
confidence: 99%
“…6,7 Interestingly, recent studies have shown that elevated systolic BP is present in almost all individuals with newly diagnosed DM. 8 One can only guess the future perspectives and magnitude of the situation given the global prevalence of DM and projections for 2030, 9 as well as the global challenge of hypertension over the next couple of decades.…”
mentioning
confidence: 99%
“…According to investigations, obesity increases the risk of diabetes and the risk of developing hypertension. Diabetes and hypertension commonly coexist; the appearance of both is common in elderly people [14] [15]. The predicates obtained in this experiment reflect the real characteristics of diabetes, or at least show many similarities to the characteristics of the illness.…”
Section: Resultsmentioning
confidence: 78%
“…The DASH (dietary approaches to stop hypertension) study demonstrated that a diet high in whole grains, fruit, vegetable and low fat dairy, and restricted in fat, lowers BP in hypertension individuals. Dietary consumption of oats is consistent with the DASH recommendations, and may confer benefit due to its fiber content (Contreras et al, 2000).…”
Section: Blood Pressure and Oat β-Glucanmentioning
confidence: 67%